THE ENTANGLEMENT OF VIOLENCE AND MODESTY: A STRUCTURAL ANALYSIS OF VIOLENCE AGAINST WOMEN IN INDIA: A Structural Analysis of Violence Against Women in India (Proceedings of the World Conference on Women’s Studies, 2026)
This paper examines the structural relationship between female modesty norms and gender-based violence in contemporary India. It aims to clarify how cultural ideals of female modesty intersect with institutional responses to violence, reinforcing women’s vulnerability within both social and legal frameworks. Drawing on court verdicts, legal reforms, and public discourses surrounding gender and violence, the paper analyzes how social expectations of purity, sacrifice, and silence operate not merely as personal virtues but as mechanisms of regulation that shape women’s treatment in society. Applying Kate Manne’s feminist theory of misogyny, it conceptualizes misogynistic violence not as an aberration but as a structural response to perceived violations of patriarchal modesty norms. The paper concludes that these norms normalize and justify harm,  rendering violence seemingly deserved or invisible, and expose a paradox in which the legal system simultaneously condemns violence while legitimizing the social ideals that sustain it.
Keywords: gender-based violence; modesty; legal discourse; patriarchy; misogyny; India